OP0299 Serum and glomerular expression of IL32 in lupus nephritis. (15th June 2017) - Truglia, S; Alessandri, C; Ciccia, F; Rizzo, A; Colasanti, T; Miranda, F; Spinelli, FR; Ceccarelli, F; Triolo, G; Capozzi, A; Sorice, M; Valesini, G; et al.
Abstract : Background: Lupus nephritis (LN) is one of the most severe features of systemic lupus erythematosus (SLE). Several cytokines and chemokines are secreted locally in case of glomerular inflammation. Interleukin 32 (IL32) is a newly described cytokine that exhibits several properties typical of proinflammatory cytokines. Ex vivo and in vitro studies supported the role of Toll like receptors (TLRs) in LN pathogenesis and recent investigations demonstrated that Poly I:C, a ligand for (TLR) 3, strongly induced IL32 production from several cell populations. Objectives: To investigate serum and urinary levels of IL32 in a cohort of LN patients compared to SLE patients without renal involvement and healthy controls (HC). In addition, we investigated kidney expression of IL32 and in vitro ability of LN patients' serum IgG to stimulate IL32 production by TLR3 activation in human embryonic kidney 293 cells line stably transfected with a TLR3 plasmid (Hek293/T3). Methods: Serum and urinary IL32 concentrations were measured using ELISA; a polyclonal rabbit anti-human IL32 was used to evaluate the expression of IL32 in renal biopsies. To assess the production of IL32 induced by patients' IgG and the transduction pathway of TLR3 we performed Western Blot analysis for IL32, TBK1 and NFkB. Results: We recruited 60 LN patients, 50 SLE patients without renal involvement and 30 HC; 40 LN patients had an active disease (a-LN) and the remaining 20 were in remission (r-LN). IL32 serum levels were significantly higher in patients with r-LN (median 1368, IQR 3910) and HC (median 721, IQR 2271) compared to SLE patients without renal involvement (median 203, IQR 662.8 pg/ml) (p=0.03 and p=0.018, respectively). There were no significant differences in urinary IL32 levels among LN patients, SLE patients without renal involvement and HC. In LN patients a direct association between IL32 serum levels and disease duration (p=0.02; r 0.2978) was observed. Immuno-histochemical analysis performed on renal biopsies of 20 a-LN and 8 HC showed that IL32 was strongly expressed in renal samples of LN patients, especially in patients with class IV, compared to controls. Western Blot analysis showed that antibodies isolated from LN patients induced in vitro production of IL32 in Hek293/T3 cells as well as the phosphorylation of NFkB and TBK1. Conclusions: The results of the present study show increased IL32 serum levels in r-LN patients as well as increased expression of such cytokine in renal tissues of a-LN patients. IL32 renal expression and its production by Hek293/T3 cells after patients' IgG stimulation, probably mediated by TLR3, may suggest the production of IL32 directly at renal level in course of LN. Disclosure of Interest: None declared